(untitled) (REMUNOM, 2025)
Safe surgery is a crucial aspect of healthcare, especially in surgical procedures, where patient safety must be a priority. Nursing staff play an essential role in promoting patient safety throughout the surgical process, from preoperative preparation to postoperative care. The concept of "safe surgery" encompasses a set of practices and protocols that aim to prevent complications and ensure the physical integrity of the patient. This includes correct patient identification, verification of necessary materials, and adherence to aesthetic procedures. Nursing is essential in implementing safety protocols, such as verifying the patient’s identity, administering medications, and monitoring specific signs, which help detect potential complications before and during surgery. In addition, nurses actively collaborate in educating patients about the procedure and postoperative guidelines, ensuring comprehensive and continuous care. Studies show that adherence to safety measures, such as the use of surgical checklists, has contributed significantly to reducing medical errors, preventing adverse events, and improving the quality of care. The implementation of a safety culture that involves the entire team is essential to reduce risks during surgery and to promote a safer and more effective care environment. Based on this information, this study is based on a literature review, with the objective of analyzing and synthesizing the practices and protocols adopted by the nursing team to ensure patient safety during the surgical procedure. The research seeks to identify the main strategies used to minimize risks and complications, in addition to highlighting the importance of adherence to safety measures, such as surgical checklists, and the impact of nursing performance in reducing medical errors and adverse events. Through the literature review, we hope to offer a comprehensive view of safety practices in the surgical environment and provide support for the continuous improvement of health care.